2020
DOI: 10.3389/fonc.2020.575422
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Model Based on CXCL8-Derived Radiomics for Prognosis Prediction in Colorectal Cancer

Abstract: Introduction: Prognosis prediction is essential to improve therapeutic strategies and to achieve better clinical outcomes in colorectal cancer (CRC) patients. Radiomics based on high-throughput mining of quantitative medical imaging is an emerging field in recent years. However, the relationship among prognosis, radiomics features, and gene expression remains unknown. Methods: We retrospectively analyzed 141 patients (from study 1) diagnosed with CRC from February 2018 to October 2019 and randomly divided them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…Exploring the genomics of cancer patients might help to optimize therapeutic strategies. Previous study has proposed that the gene expression could be evaluated by radiomics features in CRC ( 34 ). However, the potential associations between radiomics, gene expression, and clinical risk remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the genomics of cancer patients might help to optimize therapeutic strategies. Previous study has proposed that the gene expression could be evaluated by radiomics features in CRC ( 34 ). However, the potential associations between radiomics, gene expression, and clinical risk remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The type of information provided by radiomics conceptually suggests that features not captured by current conventional image analysis methods can be extracted from existing CMR images by means of radiomics, and that this information appears to provide additional insight into myocardial microstructural remodeling patterns (28) so that models combining both radiomics and conventional imaging graphics parameters can be used to improve diagnostic performance. Previous studies (29,30) in other fields have also shown the combined model performs better than single conventional imaging or radiomics model.…”
Section: Cine Images Routinely Provide the Initial Diagnostic Impress...mentioning
confidence: 92%
“…Of the 68 studies, 13 [12,26,[61][62][63][64][65][66][67][68][69][70][71](19%) used semi-automatic segmentation, 3 [52,72,73](4%) used automatic segmentation. Except for 12 [21,25,44,45,49,53,[74][75][76][77][78][79] studies which did not describe the segmentation methods used, the remaining 40 [13-20, 22-24, 46-48, 50, 51, 54-56, 80-100]studies adopted the manual segmentation method.…”
Section: Segmentationmentioning
confidence: 99%